Nestin-Expressing Precursors Give Rise to Both Endothelial as well as Nonendothelial Lymph Node Stromal Cells - Koning, Jasper J. (J Immunol, 2016)
During embryogenesis, lymph nodes form through intimate interaction between lymphoid tissue inducer and lymphoid tissue organizer (LTo) cells. Shortly after birth in mice, specialized stromal cell subsets arise that organize microenvironments within the lymph nodes; however, their direct precursors have not yet been identified. In the bone marrow, mesenchymal stem cells are labeled with GFP in nestin-GFP mice, and we show that during all stages of development, nestin(+) cells are present within lymph nodes of these mice. At day of birth, both mesenchymal CD31(−) and endothelial CD31(+) LTo cells were GFP(+), and only the population of CD31(−) LTo cells contained mesenchymal precursors. These CD31(−)nestin(+) cells are found in the T and B cell zones or in close association with high endothelial venules in adult lymph nodes. Fate mapping of nestin(+) cells unambiguously revealed the contribution of nestin(+) precursor cells to the mesenchymal as well as the endothelial stromal populations within lymph nodes. However, postnatal tamoxifen induced targeting of nestin(+) cells in nes-creER mice showed that most endothelial cells and only a minority of the nonendothelial cells were labeled. Overall our data show that nestin(+) cells contribute to all subsets of the complex stromal populations that can be found in lymph nodes.